Improving construction machine engine system durability in Latin American conditions - Azevedo, Kurt Milward, author; Olsen, Daniel, advisor; Bradley, Thomas, committee member; Grigg, Neil, committee member; Strong, Kelly, committee member (Colorado State University. Libraries, 2018)
Between 2016 and 2030, the Latin America region needs to spend $7 trillion dollars (Bridging global infrastructure gaps, 2016). Thus, for the foreseeable future, the Latin American market will experience high demand for construction equipment such as backhoes, excavators, crawler-dozers, and loaders to construct roads, housing, airports, and sea ports. Construction equipment employed in Latin America operates in conditions which are often more severe compared to developed countries such as the United States. Consequently, the durability of construction equipment diesel engines is reduced within the context of the system engineering life cycle. This results in a greater number of warranty claims, increased customer product dissatisfaction, and delays in completing contracted projects. Peer-reviewed literature lacks information regarding the wear and failure of construction equipment diesel engines operating in Latin America. Thus, the purpose of this research is to contribute to the system and maintainability engineering fields of knowledge by analyzing oil samples taken from diesel engines operating in Latin America. Oil samples are leading indicators and predictors for wear in specific components of diesel engines, as they directly connect to the use conditions of actual work environments. The methodology approach considers data points from different sources and countries. The engine oil sample analysis results are evaluated in the context of local diesel fuel quality, machine diagnostic trouble codes, and the work environments for the following countries: Bolivia, Colombia, Costa Rica, Dominican Republic, Ecuador, Guatemala, Honduras, Mexico, Paraguay, Peru, and Uruguay. The following data sources are used to answer the research questions: (1) database of oil sample laboratories of eleven countries, (2) construction equipment diagnostic trouble codes, (3) construction equipment surveys, (3) John Deere service manager's surveys, (4) two John Deere 200D excavators, (5) engine operating data, and (6) Engine Control Unit sensor data. It is determined that cross-system contamination was key contributors of oil contamination. Contamination related to environmental conditions in which the equipment was operated is also a key factor, as there is a high statistical correlation of sodium, silicone, and aluminum oil contamination present in the oil of equipment operating at higher altitudes. It is determined that sulfur, diesel fuel quality, humidity, bio-diesel, temperature, and altitude are factors that must be considered in relation to diesel engine reliability and maintenance. The research found that by correlating the engine oil sample contamination with the environment risk drivers (a) altitude and diesel fuel quality have the greatest impact on iron readings, (b) bio-diesel impacts copper, and (c) precipitation and poor diesel quality are associated with silicon levels. Wear metals present in the oil samples indicate that scheduled maintenance frequency must not exceed 250 hours for diesel engines operating in many areas of Latin America. The leading and earliest indicator of engine wear is a high level of iron particles in the engine oil, reaching abnormal levels at 218 hours. The research found that engine idling for extended periods contributes to soot accumulation.